Exact survival probability of a time-dependent open Ising chain at zero temperature - Takayuki Suzuki (Physical Review Research)
In this study, we rigorously derived the survival probability in a time-dependent Ising chain coupled with a bosonic system at zero temperature. We found that nonadiabatic transitions can occur in finite systems due to effects of the external environment, even in parameter regions that are adiabatic in isolated systems. This phenomenon is attributed to cooperative effects similar to those in the Dicke model, becoming particularly pronounced under strong-coupling conditions. Furthermore, considering a continuous-mode boson bath, this cooperative effect can potentially enhance the accuracy of estimating the coupling strength with the environment. These findings may provide new insights and serve as a criterion for evaluating existing and future simulation methods of open many-body quantum systems.